Appraising environmental competencies in organizations: scale development and relevance for internal stakeholders - Nicholas P. Carruth; Alice F. Stuhlmacher (Frontiers in Organizational Psychology, 2025)
PurposeUnderstanding how internal stakeholders view an organization's pro-environmental impact supports understanding and coordination. These stakeholder appraisals of environmental competencies were predicted to positively relate to organizational attraction, pro-environmental self-efficacy, green behaviors, organizational commitment, and intentions to leave the organization. Being informed about an organization's environmental actions and having more organizational communication sources about sustainability were predicted to increase expressions of opinions (eco-opinions). The relationships of turnover intentions and organizational commitment with environmental competencies were predicted to be moderated by environmental beliefs, such that the relationships would be stronger the more concerned stakeholders were about the environment.MethodUsing a systems theory framework focused on psychological factors of environmental sustainability in organizations, we developed an 11-item scale of environmental competencies for organizations (ECO). Internal stakeholders appraised the effectiveness of organizations' environmental actions. The scale's relevance to the theory of planned behavior and communication literature were framed within the macro system of inputs, throughputs, and outputs of organizational environmental sustainability. A pilot test of the scale with 216 university students suggested a three-factor model for the stakeholder perceptions. Online survey responses from 587 additional participants from a different university (250 university employees and 347 students) also fit the same model and was used for hypothesis testing.ResultsAppraisals of environmental competencies were related to inputs like organizational attraction and outputs of organizational commitment, turnover intent, and increased green behaviors since joining the organization. Opinions about environmental competencies were more likely to be expressed when internal stakeholders felt informed of organizational activities and had more sources of environmental communications.ConclusionLarge-scale changes in organizations require internal coordination across multiple systems, and internal stakeholders are key to these change efforts. Evidence suggests that the ECO scale is a useful tool for organizational sustainability insights and can contribute understanding on how the psychological system relates to, as well as amplifies or derails, organizational sustainability efforts.